2016
DOI: 10.1007/s12223-016-0444-0
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Borrelia burgdorferi sensu stricto and Borrelia garinii DNAs in patient with Hyperkeratosis lenticularis perstans (Flegel disease)

Abstract: Determination of the causative agent of erythema-like skin lesions in case of nonspecific superficial perivascular dermatitis was supported by histological examination and led to the latter diagnosis of Hyperkeratosis lenticularis perstans (Flegel disease) in patient. The presence of antibodies against Borrelia burgdorferi in patient serum was confirmed by a routine ELISA method and verified by Western blot technique. Skin biopsy and blood specimens were analyzed by PCR and multilocus sequence analysis (MLSA).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Flegel’s disease (FD), first described in 1958, is a rare cutaneous disorder that usually arises in the fourth/fifth decade of life, often confused with other cutaneous keratotic pathologies. To the best of our knowledge, about 80 articles dealing with FD cases have been reported in the literature [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. According to the literature, there is a slight prevalence of the female gender with a ratio 1.6:1 and a median age of 50 years, ranging between 18 and 82 years [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flegel’s disease (FD), first described in 1958, is a rare cutaneous disorder that usually arises in the fourth/fifth decade of life, often confused with other cutaneous keratotic pathologies. To the best of our knowledge, about 80 articles dealing with FD cases have been reported in the literature [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. According to the literature, there is a slight prevalence of the female gender with a ratio 1.6:1 and a median age of 50 years, ranging between 18 and 82 years [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, about 80 articles dealing with FD cases have been reported in the literature [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. According to the literature, there is a slight prevalence of the female gender with a ratio 1.6:1 and a median age of 50 years, ranging between 18 and 82 years [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. The median duration of the disease before reaching the diagnosis is reasonably long, with a median of eight years.…”
Section: Discussionmentioning
confidence: 99%
“…No clear data are available about trigger of HLP. According to some authors, HLP may be triggered by ultraviolet radiation, 27 and a single case report verified the presence of B. burgdorferi DNA in a patient with histologically confirmed diagnosis of FD, suggesting the possibility that this spirochete could be a trigger for HLP 28 . Some authors supposed a relationship between genes participating in oncogenesis and HLP genes.…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%
“…By contrast, in older lesions because of the scarcity of inflammatory infiltrate, corticosteroids are ineffective. 5‐fluorouracil (5‐FU) cream 5%: the most consistent results have been reported with topical 5‐FU cream 5%. It has been suggested that the 5‐FU provokes a strong inflammatory response, leading to the sloughing of the HLP lesion 12,28,35 . However, some works reported a relapse after stopping the therapy 20,36 …”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%
See 1 more Smart Citation